2018
DOI: 10.1111/jop.12721
|View full text |Cite
|
Sign up to set email alerts
|

PAI‐1, CAIX, and VEGFA expressions as prognosis markers in oral squamous cell carcinoma

Abstract: Our results suggest a potential role for these expressions profiles as tumor prognostic markers in OSCC patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 26 publications
(59 reference statements)
2
29
0
Order By: Relevance
“…This was confirmed by Li and coworkers, suggesting its use as a prognostic biomarker for this disease [ 61 , 62 , 63 ]. Thus, CA IX was established as an additive prognostic marker [ 45 , 64 ]. In addition, a role of CA IX as a pH sensor was established, and the first therapeutic options by the selective inhibition of carbonic anhydrases, leading to a reversion of the multidrug resistance in tumor cells, were reported [ 65 ].…”
Section: Hif-1α Stabilization Under Normoxia Its Role In Glutaminmentioning
confidence: 99%
“…This was confirmed by Li and coworkers, suggesting its use as a prognostic biomarker for this disease [ 61 , 62 , 63 ]. Thus, CA IX was established as an additive prognostic marker [ 45 , 64 ]. In addition, a role of CA IX as a pH sensor was established, and the first therapeutic options by the selective inhibition of carbonic anhydrases, leading to a reversion of the multidrug resistance in tumor cells, were reported [ 65 ].…”
Section: Hif-1α Stabilization Under Normoxia Its Role In Glutaminmentioning
confidence: 99%
“…Out of the 1741 publications which were initially retrieved, 18 studies met our inclusion criteria and were included in the meta-analysis, as depicted in Figure 1. The studies reported on a total of 1616 OSCC-affected patients [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] .…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
“…The data was collected in a period spanning from 1987 to 2015 [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44] while the year of publication ranged from 2008 to 2019. The anatomic location of the tumours was mainly divided into exclusively tongue 27,28,30,31,37,39,42 , or mixed subsite tumours 29,[32][33][34][35][36]38,40,41 .…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Yang et al found CA9 mRNA levels as prognostically relevant using datasets from The Cancer Genome Atlas (TCGA) of patients with oral cancer [35]. Peterle et al [37] and Brockton et al [32] described the CAIX protein level to be prognostically relevant to OSCC. Lin et al found a worse outcome of OSCC patients when lipocalin 2 (LCN2) was weak but CAIX was strongly expressed [33].…”
Section: Introductionmentioning
confidence: 99%